Risk Management Analysis in Tobacco Supply Chain Using the House of Risk Method - Rini Oktavera; Kurniawan, Moch. Rosi; Saraswati, Rahayu; Sutejo, Bambang (Journal of Applied Science, Engineering, Technology, and Education, 2022)
Many risks affect the smooth flow of the supply chain, thereby necessitating numerous efforts to improve supply chain management by preventing and resolving these occurrences. Therefore, the purpose of this research was to determine the sources of possible and priority risks in the tobacco supply chain in Probolinggo Regency and design appropriate priority management strategies. This research investigated the flow of the tobacco supply chain and identified various possible risks using the Failure Modes and Effect Analysis (FMEA) method, which analyzes the impact or severity and chance of occurrence. A risk event was conducted in the plan and source process to determine the type of risk and identify the priority agents that can be reduced by the House of risk (HOR) approach. Subsequently, this research obtained 11 risk events and 20 agents, including 4 priorities for handling, alongside 4 coping strategies designed to address and reduce possible sources of risk in the tobacco supply chain